Nanoencapsulation: An efficient technology to boost the antimicrobial potential of plant essential oils in food system - Prakash, Bhanu; Kujur, Anupam; Yadav, Amrita; Kumar, Akshay; Singh, Prem Pratap; Dubey, N.K. (Food control, 2018)
Plant essential oils (EOs) possesses remarkable antimicrobial efficacy and therefore have great potential as an alternative of health hazardous synthetic preservatives. In spite of marvellous efficacy, their application yet not widely used by the food industries due to some of the major intrinsic obstacles viz., low water solubility, bioavailability, volatility and stability in the food system. The recent advancement in nanotechnology has potential to address these existing obstacles of EOs as preservatives in the food system. The applications of nanomaterials as a carrier agent of EOs recently gain momentum of interest by the food industries to improve their shelf-life and preservatives efficacy at low doses. Nanoemulsions, microemulsions, solid-lipid nanoparticles and liposomes are some of the currently used encapsulation strategies to encapsulate plant bioactive compounds. In this review, we explored the potential application of nanoencapsulated plant EOs as novel source of food preservatives. In addition, the prospects, existing limitations and future research direction for their commercialization are also discussed. •Essential oils as food preservatives: current status, challenges and significance.•Nanoencapsulation approaches to boost the preservative potential of essential oils.•Nanocarrier and techniques used for the characterization of encapsulated materials.•Mechanism of action of nanoencapsulated essential oil against food borne microbes.•Critical challenges and prospects for their applications in the food industry.